Conformed to the Image of Christ: Evaluating Approaches to Spiritual Formation - Philip Suciadi Chia; Asato Chishi (Jurnal Jaffray, 2023)
In his letter to the Church in Ephesus, Paul writes that every disciple of Jesus ought to “make God’s activity the pattern for their lives” and become Christlike by Andrew T. Lincoln. Every disciple’s goal is to imitate the perfect image of God—Jesus Christ. This imitation is possible through practical obedience, as the German theologian Dietrich Bonhoeffer stated. Keeping in mind that the disciple’s end goal is to imitate Jesus, it is deemed essential to evaluate Spiritual formational approaches that are viewed as scaffolds in conforming to the image of Christ. The research seeks to critically analyze four approaches to Spiritual formation to appreciate their strengths and identify their weaknesses and evaluate their effectiveness to determine if such approaches can help believers in conforming to the image of Christ. Thus, the thesis of this article is to argue for the quintessential role of the Holy Spirit, the essential responsibility of the human agent, and the indispensable role of the Christian community, which are deemed crucial for effective Spiritual formational approaches.